Pengembangan Kit Media untuk Merangsang Kreativitas Anak kelas 4 SD - Litha Kusuma Wardhani; Robinson Situmorang; Cecep Kustandi (Universitas Negeri Jakarta, 2018)
This development research develops media kit that used to stimulate creativity in 4th grade students of Global Kids Indonesia school. The media kit facilitate the students with material that may improve their creativity. According to its purpose, this development research categorized to Development Research of Innovative Research. This development research refers to Romwee’s developmental model that has three major stages; planning, writing, and editing. The evaluation processes consist of expert reviews; 1 material expert, 1 media expert, 1 design expert, and 10 users. Below are the following results of each stages; 93,75 from material expert, 90,0 from media expert, 82,5 from learning design expert. The score that the researcher got from field test is 99,75. Based on the results and the procedures in developing the guidelines and the product test, researcher concluded that the media kit is reliable to stimulate creativity in 4th grade student.